Sustaining Learners Interest in Physics: An Exploratory Study - Kumar, Amlesh (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Students in science consider physics to be one of the most prevalent and difficult subject. During high school, if teachers cannot sustain learners’ interest in physics, students drop out of physics for their further study. Keeping students interested in physics is essential to make learning more fruitful and enjoyable. One of the most important aspects of a student’s success in physics is ensuring that they remain interested in the subject matter. The present study was an exploratory study on sustaining learner’s interest in physics. This study collected teachers’ views and understanding on sustaining learners’ interest in physics. It had collected thoughts of 58 pre-service teachers and six in-service physics teachers from the Bhubaneswar locality. This study focused on finding the ways and means of sustaining learners’ interest in physics. The factors that sustain students‟ interest in physics had also been examined. In this investigation, a descriptive survey method was used. An open-ended questionnaire and semi structured interview as a tool were used for the present study. It had been found that learner centric teaching-learning practices, adopting various strategies and approaches in teaching physics based on content, learner and context, utilizing learning resources and community resources for teaching physics, using ICT in physics teaching-learning practices etc. by the physics teachers can sustain the learner‟s interest in physics. The study’s findings suggest implications for sustaining learners‟ interest in physics